2007
DOI: 10.1038/sj.bmt.1705618
|View full text |Cite
|
Sign up to set email alerts
|

CD34+ progenitors are reproducibly recovered in thawed umbilical grafts, and positively influence haematopoietic reconstitution after transplantation

Abstract: Cord blood (CB) units are increasingly used for allogeneic transplantation. Cell dose, a major factor for CB selection, is evaluated before freezing by each CB bank, using various techniques. This may introduce variability and affect the prediction of cell recovery after thawing, or haematopoietic reconstitution. Forty-two children were transplanted at the same institution with unrelated CB units. All units were thawed and evaluated at the same cell therapy facility, using standard procedures. We investigated:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…However, there are renal adverse events associated with the use of HES , which leads to limitation in the use and availability of this product similar to dextran 40. Other authors also report CD34 + viable cells recovery around 51·5% , 60% and other around 80% similar to our results with the experimental solution. There are consistent evidence that the number and viability of CD45 and CD34 + cells have a direct correlation on the graft success rate , indicating the relevance of optimizing CD34 + and CD45 viable cells recovery after cryopreservation and thawing.…”
Section: Discussionsupporting
confidence: 92%
“…However, there are renal adverse events associated with the use of HES , which leads to limitation in the use and availability of this product similar to dextran 40. Other authors also report CD34 + viable cells recovery around 51·5% , 60% and other around 80% similar to our results with the experimental solution. There are consistent evidence that the number and viability of CD45 and CD34 + cells have a direct correlation on the graft success rate , indicating the relevance of optimizing CD34 + and CD45 viable cells recovery after cryopreservation and thawing.…”
Section: Discussionsupporting
confidence: 92%
“…These findings have been replicated in subsequent studies to varying degrees 2,4,9,29 . In a smaller number of studies, CD34+ cell dose has been shown to predict engraftment and survival, 5‐9 but the use of CD34+ is limited by standardization issues and CD34+ enumeration is not available for a significant portion of the existing banking inventory. In addition, the precryopreservation TNC and/or CD34+ content do not necessarily reflect the overall potency of the CBU after cryopreservation, storage, and thawing.…”
Section: Discussionmentioning
confidence: 83%
“…It is believed that a significant reason for this relates to the overall quality of the cord blood (CB) graft. Attempts at correlating other graft variables, for example, CD34+ cells or colony‐forming units (CFUs), with engraftment have shown superior predictive value in limited studies, 5‐12 but no single variable has a high enough correlation with engraftment or graft failure. Furthermore, individual CBU profiles may show discordant, rather than linear, correlations of one variable compared to another.…”
mentioning
confidence: 99%
“…Thrombocytopenia occurs in many hematological diseases and also after hematopoietic stem cell transplantation, intensive chemotherapy or radiotherapy (1)(2)(3)(4)(5)(6)(7). Repeated platelet transfusion increases the risk of alloimmunization, bacterial and viral infection, and transfusion reaction (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%